Bacteriophages and their Enzymes in Biofilm Control - K. Chan, Benjamin; T. Abedon, Stephen (Current Pharmaceutical Design, 2015)
Although free-swimming planktonic bacteria historically have been the typical focus of microbiological studies, the natural state of many or most bacteria is one where they instead are associated with surfaces and/or each other. For many pathogenic as well as nuisance bacteria, including biofouling bacteria, it consequently is within the context of this biofilm state that antibacterial strategies must be implemented. For reasons that are not fully understood, however, biofilm-associated bacteria tend to be less susceptible to treatments with standard chemical antibacterial agents than are planktonic bacteria, and this appears to be especially an issue with the use of lessharsh agents such as antibiotics. Within a variety of contexts the development of less- or selectively toxic antibacterial agents capable of clearing biofilms therefore would be welcome. In this review we consider the use of three categories of such agents as anti-biofilm antibacterials. These are lytic viruses of bacteria, that is, bacteriophages, effecting phage-mediated biocontrol of bacteria (a.k.a., phage therapy); purified phage-encoded enzymes that digest bacterial cell-wall material (endolysins or simply lysins); and a second category of phage-encoded enzymes that digest the extracellular polymeric substance (EPS) that are particularly notable components of bacterial biofilms (EPS depolymerases). These agents have been shown to reduce the bacterial density of a diversity of biofilms and, in many cases, tend to be lacking in inherent toxicity against the tissues of animals. Here we consider these phage-based anti-biofilm strategies with emphasis on ecological aspects of their action and with particular consideration of EPS depolymerases.
Keywords: lysin